2017
DOI: 10.2196/mededu.7903
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Medical Oncology Training in Australian Medical Schools: Pilot Study

Abstract: BackgroundOncology is a rapidly evolving field with continuous advancements in the diagnosis and treatment of cancer. Therefore, it is important that medical students are provided with the knowledge and experience required to care for oncology patients and enable them to diagnose and manage toxicities of novel therapeutic agents.ObjectiveThis study was performed to understand the medical students’ perspective of the oncology education provided in universities across Australia and identify areas of education th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Students were unsatisfied with oncology teaching. Findings are consistent worldwide, with students reporting limited oncology specialty exposure [ 9 , 27 ]; teaching dissatisfaction [ 28 ]; and poor confidence in oncology care [ 9 , 29 , 30 ]. Newly-qualified doctors report limited undergraduate exposure to cancer patients, and lack of cancer care knowledge [ 6 , 31 ].…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Students were unsatisfied with oncology teaching. Findings are consistent worldwide, with students reporting limited oncology specialty exposure [ 9 , 27 ]; teaching dissatisfaction [ 28 ]; and poor confidence in oncology care [ 9 , 29 , 30 ]. Newly-qualified doctors report limited undergraduate exposure to cancer patients, and lack of cancer care knowledge [ 6 , 31 ].…”
Section: Discussionmentioning
confidence: 75%
“…Scarce data is available on medical students’ perspectives on current undergraduate oncology teaching with data almost non-existent for the UK [ 28 , 42 – 47 ]. To our knowledge, this is the first national cross-sectional survey of UK medical students’ views in oncology.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, medical schools typically offer limited exposure to oncology within their curriculum, often limited to a couple of weeks throughout the entire course [10,11]. Oncology is usually taught in the context of common cancer subtypes and rarely are the different treatment modalities in oncology explored in any detail [12]. Previous studies have shown that one teaching event in radiation oncology increased student confidence during oncology placements, which highlights that greater explanation of cancer care allows students to benefit from clinical attachments in oncology [13].…”
Section: Introductionmentioning
confidence: 99%
“…109 Additionally, 78% of Australian medical students reported dissatisfaction with the number of dedicated oncology teaching hours. 110 However, efforts have been made to implement some standardized curricula, with preliminary results indicating adequate direction to acquire necessary competencies, stimulus for learning opportunities, and positive contributions to participant development. 75 Reviews of European medical schools show similar results.…”
Section: General Reviewmentioning
confidence: 99%